PHYSICAL VS. DIGITAL SAFE HAVENS IN EMERGING ISLAMIC MARKETS: A COMPARATIVE ANALYSIS OF GOLD, COMMODITIES, AND CRYPTO ASSETS IN INDONESIA, MALAYSIA, AND TURKEY - Gandy Setiawan; Magita Sari; Achmad Helmi; Ahmad Rodoni (JURNAL ILMIAH EDUNOMIKA, 2026)
This study investigates the safe-haven properties of physical assets (Gold, Commodities) versus digital assets (Crypto, Shariah-compliant Tokens) for Islamic equity markets in Indonesia, Malaysia, and Turkey during the 2020–2025 monetary tightening era. Utilizing weekly data, the study employs Dummy Augmented Regression and Portfolio Weight Optimization to isolate asset correlations during extreme market downturns and simulate hedging effectiveness. The results reveal a "Shariah Crypto Paradox," where Shariah-compliant tokens fail to provide stability and instead act as risk amplifiers. Similarly, Gold fails as a safe haven due to monetary-induced contagion. Conversely, real commodities (CPO/Soybean) demonstrate superior defensive qualities, validating the "natural hedge" hypothesis for producer nations. This research challenges the "Digital Gold" narrative by empirically proving that Shariah compliance in crypto does not mitigate market volatility. It proposes a "Satellite Strategy" focusing on real commodities over digital assets for Islamic portfolio resilience.